Dampak Intervensi Eksternal Lembaga Non-Pemerintah terhadap Tingkat Stres Kerja dan Efektifitas Kepemimpinan - Ratna Bintari, Dewi Masithoh; Mulyaningtyas, Ratna Dewi (Otonomi, 2026)
This study aims to analyze the influence of external interventions by non-governmental organizations (NGOs) on the work stress level and leadership effectiveness of principals at public senior high schools in Kediri Regency and Kediri City. NGO interventions that often exceed the limits of social oversight have resulted in increased psychological pressure and disruptions to school leadership performance. This research employs a quantitative approach using the Partial Least Square (PLS) method, supported by qualitative data from in-depth interviews. The results show that external intervention by NGOs has a positive and significant effect on the work stress levels of school principals, indicated by a t-statistic value of 5.123 and a p-value < 0.05. However, the influence of such interventions on leadership effectiveness was not statistically significant, with a t-statistic of 1.763 and a p-value > 0.05. In-depth interviews reinforced these findings, revealing that school principals experience various forms of pressure, threats, and discomfort due to NGO interference, although they continue to uphold professional and regulation-based leadership. This study highlights the urgent need for clear regulations and boundaries regarding the role of NGOs in educational environments to ensure their presence supports educational quality rather than creating psychological burdens that interfere with school management